2010
DOI: 10.1016/j.jacc.2009.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Coronary Calcium Conversion Among Patients With a Normal Coronary Calcium Scan

Abstract: Among individuals with CAC = 0, conversion to CAC >0 is nonlinear and occurs at low frequency before 4 years. No clinical factor seems to mandate earlier repeat CAC scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(103 citation statements)
references
References 28 publications
9
91
3
Order By: Relevance
“…First, we used appropriate methods to minimize the interscan variability. Second, it has been shown that CAC does not increase at a constant rate and usually progression is detected following a ‘lag period' of 4 years [16]. In our study, all patients had the second scan at least 4 years after the first one.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…First, we used appropriate methods to minimize the interscan variability. Second, it has been shown that CAC does not increase at a constant rate and usually progression is detected following a ‘lag period' of 4 years [16]. In our study, all patients had the second scan at least 4 years after the first one.…”
Section: Discussionmentioning
confidence: 62%
“…For instance, according to a multi-ethnic study of atherosclerosis in younger age patients (closer to our study population's age range) the yearly rate of CAC incidence was <5%. However, because of the non-linear nature of CAC progression and the ‘lag period' before the detection of the new CAC, using an annual incidence rate of CAC might not be a good measure to assess CAC progression [16]. Moreover, the analysis of raw CAC data does not take the high interscan variability into account.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies in CAC progression on KTRs could be partially related to demographic and clinical differences of the study populations, but there are some other variables that should be considered in CAC progression studies: (1) interscan variability of CAC scoring; (2) a CAC score reflects the aggregate of medial and intimal wall calcification: a different progression pattern can be expected for each type of calcification, and (3) the optimal time interval for measuring CAC progression is not defined. For the purpose of interventional trials, intervals of at least 3 years were proposed [20]. The time interval for measuring CAC progression is critical in transplantation where the risk factors relating to it start at the time of surgery.…”
Section: Vascular Calcification Progression and Cardiovascular Outcomesmentioning
confidence: 99%
“…Currently, coronary calcium scan as well as coronary angiography scan has become an important methodology for screening or monitoring patients with suspected CAD or coronary revascularization [37]. The optimal followup interval using CAC scan, QCT and DXA for patients with osteoporosis and atherosclerosis has been still ambiguous [102,103]. A study by Lenora et al [104] displayed the follow-up intervals (least significant change/median rate of a BMD change) in both women and men as 8 years and 13 years, respectively, by using a DXA scanner, 3 and 32 years by using a lunar Prodigy scanner for total hip and lumbar spine respectively.…”
Section: Follow-up Time Using the Qctmentioning
confidence: 99%